1978
DOI: 10.1128/jvi.28.1.375-386.1978
|View full text |Cite
|
Sign up to set email alerts
|

Homologous interference mediated by defective interfering influenza virus derived from a temperature-sensitive mutant of influenza virus

Abstract: A temperature-sensitive group II mutant of influenza virus, ts-52, with a presumed defect in viral RNA synthesis, readily produced von Magnus-type defective interfering virus (DI virus) when passed serially (four times) at high multiplicity in MDBK cells. The defective virus (ts-52 DI virus) had a high hemagglutinin and a low infectivity titer, and strongly interfered with the replication of standard infectious viruses (both ts-52 and wild-type ts+) in co-infected cells. Progeny virus particles produced by co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
1

Year Published

1979
1979
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 31 publications
2
72
1
Order By: Relevance
“…The presence of defective influenza genomes has been well characterized in cell cultures (27) and animal models (25). Influenza DVGs have also been observed in clinical human H1N1 samples (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of defective influenza genomes has been well characterized in cell cultures (27) and animal models (25). Influenza DVGs have also been observed in clinical human H1N1 samples (8).…”
Section: Discussionmentioning
confidence: 99%
“…Influenza defective viral genomes (DVGs) were first reported by von Magnus (1) and have since been characterized in vivo during high multiplicity of infection (MOI) passage studies (27) as well as from clinical human samples (8, 9). DVGs are classified as viral genomes harboring mutations which render them incapable of self-replication.…”
Section: Introductionmentioning
confidence: 99%
“…With influenza, von Magnus (26) originally described the formation of noninfectious virus by successive high-multiplicity undiluted passages of virus in embryonated eggs. Recently we and others have reported the presence of small deleted RNA segments (DI RNA) in DI influenza viral preparations (5,17,19,20,22). Furthermore, based on several lines of evidence (albeit indirect), we have postulated that, as in the case of other viruses, these DI RNA molecules are responsible for DI virus-mediated interference.…”
mentioning
confidence: 94%
“…They interfere with the replication of homologous infectious viruses at the level of synthesis of virus-specified RNA (7). Nayak et al (1978) reported that DI particles of a temperature-sensitive mutant of WSN influenza virus, produced by successive undiluted passage in MDBK cells, did not inhibit the synthesis of cRNA of standard virus but inhibited specifically vRNA synthesis. In the present study, it seems most likely that noninfectious virus particles contained in the von Magnus virus preparation inhibited the synthesis of vRNA by coexisting infectious virus.…”
Section: Discussionmentioning
confidence: 99%
“…The other is a slowly sedimenting peak (fractions 11-15) whose radioactivity was as much as that in fractions 11-15 of standard virus-infected cells. The von Magnus incomplete virus is known to have small RNA molecules that are not present in the standard influenza virus (7,13,14,16). Small-sized RNPs containing this kind of RNA molecules may exist in these fractions although further experiments are needed to confirm this possiblity.…”
Section: Intracellular Distribution If Viral Rnp and Soluble Npmentioning
confidence: 99%